(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The report examines the behavior of a 7.62x39 bullet in a water environment and the changes in the created cavitation cavity when the geometric and mass characteristics are altered. The studies are conducted through virtual prototypes and CFD (Computational Fluid Dynamics) analyses in a SolidWorks environment, with the density of the water around the projectile and the angle of the formed cavitation cavities being the control parameters. The results indicate that the placement of the radial slit channel in the middle of the ogive part yields the best results for the angle of the cavitation cavity, which helps reduce the friction forces on the projectile, thereby increasing its linear progression in a water environment.